A Comparative Study on Loadings of the Lower Extremity during Deep Squat in Asian and Caucasian Individuals via OpenSim Musculoskeletal Modelling. (4th July 2020) - Lu, Yichen; Mei, Qichang; Peng, Hsien-Te; Li, Jianshe; Wei, Chen; Gu, Yaodong
Abstract : Populations of different ethnicities may present different movement capacities and muscular function adaptations. The purpose of this study was to investigate the differences of motion and loading in the lower extremity during dynamic deep squats between Asian and Caucasian individuals using OpenSim modelling technique with a customized squat-specific musculoskeletal model. Twenty-four participants joined the test performing the step-squat test, with right foot stepping side, squatting, and returning. The one-dimensional statistical parametric mapping package was used for statistical analysis. The main findings of the current study were as follows: (1) significant lower squat depth was observed in the Asian individuals, (2) the greater knee range of motion and contact forces were found in the Asian individuals, and (3) the greater ankle contact forces in the Caucasian individuals were notable while performing the deep squat compared to the Asian group. Knowledge found in the current study may provide implication for exercise practitioners and physiotherapists while designing schemes for the prevention of loading accumulation in the lower extremity.